Validation of cold chain during distribution of parenteral nutrition - Federico Tuan; Virginia Perone; Rocio Verdini; Maria Betina Pell; Maria Luz Traverso (Farmacia Hospitalaria)
Objective: this study aims to demonstrate the suitability of the process used to condition the extemporaneous mixtures of parenteral nutrition for distribution, considering the objective of preserving the cold chain during transport until it reaches the patient, necessary to ensure stability, effectiveness and safety of these mixtures. Method: concurrent validation, design and implementation of a protocol for evaluating the process of packaging and distribution of MNPE developed by a pharmaceutical laboratory. Running tests, according to predefined acceptance criteria. It is performed twice, in summer and on routes that require longer transfer time. Evaluation of conservation of temperature by monitoring the internal temperature values of each type of packaging, recorded by data loggers calibrated equipment. Results: the different tests meet the established criteria. The collected data ensure the maintenance of the cold chain for longer than the transfer time to the most distant points. Conclusions: this study establishes the suitability of the processes to maintaining the cold chain for transfer from the laboratory to the patient pharmacist. Whereas the breaking of cold chain can cause changes of compatibility and stability of parenteral nutrition and failures nutritional support, this study contributes to patient safety, one of the relevant dimensions of quality of care the health.